5 Oral selective tyrosine kinase 2 (TYK2) inhibition with BMS-986165 in patients with systemic lupus erythematosus: a phase 2, randomized, double-blind, placebo-controlled study (PAISLEY). (April 2019) - Singhal, Shalabh; Shah, Vaishali; Crater, Chris; Hobar, Coby; Nguyen, Hoang; Throup, John; Banerjee, Subhashis; Merrill, Joan T
Abstract : Background: Systemic lupus erythematosus (SLE) is a complex autoimmune disease, characterized by unpredictable organ and tissue involvement. Immunosuppressive drugs and corticosteroids (CS) are central to control serious SLE flares, but long-term use is associated with significant morbidity and may obscure distinctions between investigational treatments and placebo. BMS-986165 is an oral, selective TYK2 inhibitor that blocks cytokine signaling pathways key to SLE pathophysiology. A phase 2 trial of this agent is underway, designed to address some of these issues seen in lupus trials. Methods: In this randomized, double-blind, placebo-controlled, global study (ClinicalTrials.gov: NCT03252587 ), adults diagnosed with SLE at least 24 weeks before screening, and with antinuclear antibody titer of 1:80 or who were positive for anti-double-stranded DNA or anti-Smith antibodies, are being randomized (1:1:1:1) to placebo or 1 of 3 doses of BMS-986165 (figure 1 ). The primary endpoint is the SLE Responder Index 4 (SRI-4) response rate at Week 32. Secondary endpoints include Cutaneous Lupus Erythematosus Disease Area and Severity Index (CLASI) response rate, British Isles Lupus Assessment Group-based Composite Lupus Assessment response rate, both at Week 32, and safety. Key inclusion criteria include SLE Disease Activity Index 2000 (SLEDAI-2K) of 6 points, with active joint and/or skin involvement. Eligible patients must have received standard of care background immune modulators for 12 weeks. CS are permitted. Trial designs that encourage CS tapering or other limitations to background treatments have been associated with increased discrimination between treatments and placebo by lowering relative rates of placebo responses. In the current study, CS tapering is required for all patients whose disease has not worsened. Results: Planned enrollment is 360 patients (90 per cohort) at approximately 170 sites in 15 countries. A monitored review of medically appropriate disease activity scoring and tapering of CS is a part of the administration of this trial. Accrual into the PAISLEY study is ongoing. Conclusions: This study will characterize the efficacy and safety of BMS-986165, which works by a novel mechanism of TYK2 inhibition, in patients with moderate to severe manifestations of SLE. Funding Source(s): Bristol-Myers Squibb